The Enigma of Ethics: Code of Ethics Enforcement on Covid-19 Health Protocol - Fradhana Putra Disantara; Ruetaitip Chansrakaeo; Mohamad Jazuli; Ni Putu Ratnayutika; Rini Triastutiek Umiasih; Claudya Inamas Putri (Universitas Muhammadiyah Sumatera Utara, 2022)
Ethics as a guide for human behavior is often alienated in the political realm. However, the political process requires ethics to maintain the essence of the implementation of a dignified democracy. This legal research uses a conceptual approach and legislation using primary legal materials and secondary materials. The purpose of this study is to analyze the dynamics of the existence of the application of ethics in the political realm; then, review the validity of the COVID-19 health protocol as one of the codes of ethics for the organs of the Local Leaders Election (Pemilukada) organizers. The results of the study explain that in fact, ethics in the political realm is a fundamental thing that aims to provide welfare for the wider community. Furthermore, the determination of the COVID-19 health protocol as a code of ethics for the organs of the Pemilukada by the DKPP is very appropriate and legally justified; considering that DKPP has the authority to formulate and stipulate a code of ethics for the organs of the Pemilukada. Thus, it is necessary to formulate a joint regulation between the organs of the Pemilukada regarding the determination of the code of ethics for the Pemilukada.